Health-related knowledge and preferences in low socio-economic kindergarteners - Nemet Dan; Geva Deganit; Meckel Yoav; Eliakim Alon (BMC, 2012)
Abstract Objective The aim of the present study was to determine physical activity (PA) and nutrition knowledge and preferences in low socio-economic status kindergarten children. Methods Following height and weight measurement, 795 low socio-economic status kindergarten children (age 3.8-6.8 y.o) completed a photo-pair knowledge and preferences food and exercise questionnaire. Results No difference was found between nutrition and PA knowledge scores (52.3 ± 0.9 versus 52.6 ± 0.8%, respectively). There was no difference between the nutrition knowledge and preference score (52.3 ± 0.9 versus 50.9 ± 0.9%, respectively). PA preference was significantly higher than knowledge (56.9 ± 1.5 versus 52.6 ± 0.8%, respectively; p < 0.0001). Significant correlations were found between nutrition knowledge and preferences (r = 0.55, p < 0.0001), physical activity knowledge and preferences (r = 0.46, p < 0.0001), and nutrition and PA preferences (r = 0.46, p < 0.001). Nutrition preference scores were significantly lower in overweight compared to normal weight kindergartners 48.1 ± 1.7 versus 52.0 ± 1.0%; p < 0.05). PA knowledge and preference scores were significantly higher among male compared to the female kindergartners (p < 0.001 for both). Conclusion Our data demonstrate diversities in physical activity and nutrition knowledge and preferences among low socio-economic status kindergarten children. These findings may be important for the development of health promotion programs in low socioeconomic kindergarten children.